2004
DOI: 10.1590/s0103-84782004000400007
|View full text |Cite
|
Sign up to set email alerts
|

Épocas e métodos de aplicação de nitrogênio em milho cultivado no sistema plantio direto

Abstract: Timing and methods of nitrogen application for corn under no-tillage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Yamada (1996) reports that N deficiency in the initial stage of corn development compromises plant development and reduce the number of ears eggs, thereby reducing production. Further, according Pöttker and Wiethölter (2004), if not limited by other factors, the greater N availability increases the potential of the plant to set greater number and weight of grains per spike. Oliveira and Caires (2003) also reported that the increase in N levels (0 to 120 kg ha -1 ) increased linearly the number of grains per ear (Ŷ = 501.5 + 0.26x), weight of thousand grains (Ŷ = 356.0 + 0.20x) and corn yield (Ŷ = 6595.00 + 15.59x).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada (1996) reports that N deficiency in the initial stage of corn development compromises plant development and reduce the number of ears eggs, thereby reducing production. Further, according Pöttker and Wiethölter (2004), if not limited by other factors, the greater N availability increases the potential of the plant to set greater number and weight of grains per spike. Oliveira and Caires (2003) also reported that the increase in N levels (0 to 120 kg ha -1 ) increased linearly the number of grains per ear (Ŷ = 501.5 + 0.26x), weight of thousand grains (Ŷ = 356.0 + 0.20x) and corn yield (Ŷ = 6595.00 + 15.59x).…”
Section: Discussionmentioning
confidence: 99%